Spinal stability analysis of lumbar interbody fusion according to pelvic type and cage angle based on simplified spinal model with various pelvic indices - Kim, Cheol-Jeong; Son, Seung Min; Choi, Sung Hoon; Ryu, Dongman; Lee, Chiseung (Frontiers in Bioengineering and Biotechnology, 2022)
Recently, the objectives of lumbar interbody fusion(LIF) have been extended to include the correction of broader/relative indications in addition to spinal fixation. Accordingly, LIF must be optimized for sagittal alignment while simultaneously achieving decompression. Therefore, a representative model classified into three pelvic types, i.e., neutral pelvis(NP), anterior pelvis(AP), and retroverted pelvis(RP), was selected according to the pelvic index, and LIF was performed on each representative model to analyze Lumbar lordosis(LL) and the corresponding equivalent stress. The finite element(FE) model was based on a sagittal 2D X-ray image. The calculation efficiency and convergence were improved by simplifying the modeling of the vertebral body in general and its posterior portion in particular. Based on the position of the pelvis, according to the pelvic shape, images of patients were classified into three types. Subsequently, representative images were selected for each type. The fixation device used in the fusion model was a pedicle screw and a spinal rod of a general type. PEEK was used as the cage material, and the cage shape was varied by using three different cage angles: 0°, 4°, and 8°. Spinal mobility: The pelvic type with the highest range of motion(ROM) for the spine was the NP type; the AP type had the highest LL. Under a combination load, the NP type exhibited the highest lumbar flexibility(LF), which was 2.46° lower on average compared to the case where a pure moment was applied. Equivalent stress on the spinal fixation device: The equivalent stress acting on the vertebrae was lowest when cage 0 was used for the NP and AP type. For the RP type, the lowest equivalent stress on the vertebrae was observed when cage 4 was used. Finally, for the L5_upper_endplate, the stress did not vary significantly for a given type of cage. In conclusion, there was no significant difference in ROM according to cage angle, and the highest ROM, LL and LF were shown in the pelvic shape of NP type. However, when comparing the results with other pelvic types, it was not possible to confirm that LF is completely dependent on LL and ROM.